OSMAN BEDRÜDDİN ERZURUMİ`NİN GÜLZAR-I SAMİNİ`SİNDE BULANAN AYETLERİN TASAVVUFİ YORUMLARI VE RUHUL-BEYAN ADLI TEFSİRLE KARŞILAŞTIRILMASI - TÜRKMEN, ENVER (Fırat Üniveristesi, 2007)
Osman Bedrüddin Erzurumû, Erzurum'da doğmuş, ancak hayatının büyük birkısmını Elazığ'da geçirmiş bir mutasavvıftır. Kendisini iyi yetiştirmiş ve kaliteli insanyetiştirmenin mücadelesini vermiştir.Tezimize konu olan eser, onun müntesiplerine yaptığı gönül sohbetlerindenkaleme alınmıştır. Açıklamasını yaptığı her ayetin Batınû tefsiri üzerinde mutlakadurmuştur. Ayetin zahirine çoğunlukla değinmiş, bazen de iniş sebebini zikretmiştir.Bu tezde; ?Gülzar-ı Saminû? adlı eserde tefsir edilen ayetler üzerindedurulmuştur. Bursevû'nin ?Ruhu'l-Beyan? adlı tefsiri ile kıyaslanmaya çalışılmıştır.Mümkün mertebe ?Letaifu'l-İşarat? adlı işarû tefsirden de faydalanılmıştır. Yapılantefsirlerden dersler çıkartılmaya çalışılmış ve ayetin zahirine ve İslam akidesine uygunbulunmayan yorumlara da işaret edilmiştir.Müellifin eserindeki yorumlar güzel bir işarû tefsir örneğidir. İnsanın gönüldünyasına hitap etmektedir. Her şeyin maddi bir meta ile ölçüldüğü günümüzde, gönüldünyamıza hitap eden, gönül erlerine olan ihtiyacımız her zamankinden daha çoktur.Anahtar Kelimeler: Allah, tefsir, batını tefsir, zahir, nefis.

Osman Bedrüddin Erzurumi was born in Erzurum, but he was a sufi who spent agreat part of his life in Elazig. He was well-educated and struggled for educating thebest people (person).The book, which is the subject of this thesis, has been written from his mindtalks to those who are following his ideas. He dwelt certainly on the esotericinterpretation (or commentary) of each versa that he explained. He touched mainly onexternal of a versa and also mentioned sometimes the reason of being sent.In this thesis, it has been dwelled on the verses interpreted from the book called?Gulzar-ı Samini?. The book has been compared whit the commentary named as?Ruhu?l-Beyan? of Bursevi. It has also been utilized from the source of the comment?Letaifu?l-İşarat? as much as possible. Some results (or lessons) have been extractedfrom the comments done, and the comments that are not in agreement with the truthpath of Islam have also been pointed out.The interpetations in the book of Author is a very nice example of işaricomment. It addresses to the heart world of human mind. Nowadays, since the value ofeverything is based on matter no doubt we need to the mind of males at the present lifemore than ever.KEY WORDS: God, commentary, esoteric interpretation, evident, mind, excellent.
Sufistic interpretations of the versas existed in Osman Bedruddin Erzurumi, Gulzar-i Samini and their comparison with the commentary named Ruhul-Beyan
Keywords: Din